Remote sensing - Sholarin, E.; Awange, Joseph (2015)
© 2015, Springer International Publishing Switzerland. Remote sensing is defined as the art, science and technology through which the characteristics of object features/targets either on, above or even below the earth’s surface are identified, measured, and analyzed without direct contact existing between the sensors and the targets or events being observed, see e.g., Jensen (Remote sensing of the environment: an earth resource perspective, 2009), Lillesand et al.(Remote sensing and image interpretation, 2010), Richards (Remote sensing digital image analysis: an introduction, 1994), Murai (GIS work book: fundamental and technical courses, vols 1 and 2, 1999) etc.This allows for information about such object features to be obtained by sensing and recording reflected or emitted energy and processing, analyzing, and applying that information.